EDUKASI PERILAKU HIDUP BERSIH DAN SEHAT DI TK ANDRI DESA ULU AER - Nurfitryani Siregar; Masria Hasibuan; Nahdia Syafitri Harahap; Royani Hasibuan; Damayanti Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to describe the implementation of clean and healthy living behavior (PHBS) education at TK Andri in Ulu Aer Village, Sosopan District, Padang Lawas Regency. A descriptive qualitative method was applied, with data collected through observation, interviews, and documentation. The research subjects consisted of the principal, teachers, and students’ parents. Data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings indicate that PHBS education was carried out through habituation of healthy practices, such as proper handwashing, maintaining school environmental hygiene, and fostering nutritious eating habits. Teachers acted as key role models and facilitators, while parental involvement strengthened the implementation at home. Although limited facilities and varying parental understanding posed challenges, the program remained effective through strong collaboration between the school and families. Consistent PHBS education successfully fostered awareness and shaped early childhood students’ character to care for personal and environmental health.